Circulating Microrna-146a as A Biomarker Related To Inflammation in Thalasemia Patients
This study delves into the intricate realm of microRNAs (miRNAs), non-coding RNA molecules that wield significant influence in the pathogenesis of various disorders. With the advent of advanced technologies, accurate quantification of miRNA abundance across diverse tissues is now attainable. Notably, extracellular circulating microparticles have emerged as robust, stable indicators for blood-based disease diagnostics. This investigation explores the dynamic interplay between circulating microparticles and clinical phenotypes, offering valuable insights into disease intricacies. The research narrows its focus to recent developments in employing circulating microparticles as biomarkers for prevalent inflammatory disorders, including infections endemic to thalassemia patients in the city of Diwaniyah, Iraq. Current findings paint a promising future for the utilization of circulating microparticles in the management of inflammatory diseases. In conclusion, this comprehensive exploration of miRNA’s regulatory role in globin gene expression has the potential to revolutionize the landscape of thalassemia, ameliorating clinical manifestations and symptoms of this debilitating hemoglobinopathy. The identification of miRNAs implicated in the disease’s pathophysiology not only paves the way for novel diagnostic markers but also opens new horizons for therapeutic interventions. Highlights : <div class="group w-full text-token-text-primary border-b border-black/10 gizmo:border-0 dark:border-gray-900/50 gizmo:dark:border-0 bg-gray-50 gizmo:bg-transparent dark:bg-[#444654] gizmo:dark:bg-transparent" data-testid="conversation-turn-15"> <div class="flex flex-1 gap-4 text-base mx-auto md:gap-6 gizmo:gap-3 gizmo:md:px-5 gizmo:lg:px-1 gizmo:xl:px-5 md:max-w-2xl lg:max-w-[38rem] gizmo:md:max-w-3xl gizmo:lg:max-w-[40rem] gizmo:xl:max-w-[48rem] xl:max-w-3xl